2014
DOI: 10.1167/iovs.13-12251
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Lymphatic Valve Formation in Relation to Lymphangiogenesis

Abstract: This study presents new insights into corneal lymphatic valve formation and function in inflammatory LG. Further investigation on lymphatic valves may provide novel strategies to interfere with lymphatic maturation and function and to treat lymphatic-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Particularly, Bazigou et al 23 examined lymphatic valve formation in Itga-9 knockout mice and reported reduced number of valves, but not lymphatic vessels, in Itga-9 homozygotes. One possible explanation for our in vivo data with the neutralizing antibody is that Itga-9 is more highly expressed on corneal lymphatic valves than vessels, 16,17 which may render the valves more sensitive to the anti-Itga-9 treatment. This warrants further investigation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Particularly, Bazigou et al 23 examined lymphatic valve formation in Itga-9 knockout mice and reported reduced number of valves, but not lymphatic vessels, in Itga-9 homozygotes. One possible explanation for our in vivo data with the neutralizing antibody is that Itga-9 is more highly expressed on corneal lymphatic valves than vessels, 16,17 which may render the valves more sensitive to the anti-Itga-9 treatment. This warrants further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…[12][13][14][15] More recently, we have reported that corneal lymphatic vessels develop luminal valves as inflammatory LG proceeds, and these valves, consisting of endothelial layers, express integrin a9b1 (Itga-9), and function to direct lymph flow in inflamed corneas. 16,17 However, the direct role of Itga-9 in corneal lymphatic valve formation and lymphatic endothelial cell (LEC) function still remain to be elucidated, which is the focus of this study. Answers to these questions are essential for developing new therapeutic strategies for lymphatic diseases.…”
mentioning
confidence: 99%
“…79 Briefly, whole-mount full-thickness corneas were harvested at 8 weeks after transplantation and fixed in acetone for immunofluorescent staining. Samples were sequentially incubated with purified rabbit anti-mouse LYVE-1 (Abcam, Cambridge, MA, USA) antibody and goat anti-mouse Itga-9 antibody (R&D Systems, Minneapolis, MN, USA), which were visualized by FITC-conjugated donkey anti-rabbit and Cy3-conjugated donkey anti-goat secondary antibodies (Jackson ImmunoResearch Laboratories), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…79 It is yet to be determined whether an intervention of the formation of these lymphatic valves, or valvulogenesis (VG), can modulate transplant survival, which is a focus of this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation